1979
DOI: 10.1073/pnas.76.8.3673
|View full text |Cite
|
Sign up to set email alerts
|

Proton nuclear magnetic resonance investigation of structural changes associated with cooperative oxygenation of human adult hemoglobin

Abstract: The structural changes associated with cooperative oxygenation of human adult hemoglobin as a function of oxygen saturation in aqueous media at neutral pH and at 25-270C have been investigated by high-resolution proton nuclear magnetic resonance spectroscopy at 250 and 360 MHz. By monitoring the intensities of two hyperfine shifted proton resonances (at about -12 and -18 ppm from H20) and two exchangeable proton resonances (at alut -6.4 and -9.4 ppm from H20) as a function of oxygenation, the amount of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 19 publications
8
29
0
Order By: Relevance
“…(ii) We constrained the ratio of probabilities of binding oxygen by the a and 8 chains to be 1.0 ± 0.05 in the range between zero and half-saturation of tetramers, in accord with the results of NMR determinations (34,35). xiii) At pH 7.4 the change in quaternary structure with fractional saturation of tetramers Y4 was constrained to be linear to within 5% between Y4 = 0 and Y4 = 0.5, in accord with results of NMR determinations (34).…”
Section: (31)supporting
confidence: 48%
See 2 more Smart Citations
“…(ii) We constrained the ratio of probabilities of binding oxygen by the a and 8 chains to be 1.0 ± 0.05 in the range between zero and half-saturation of tetramers, in accord with the results of NMR determinations (34,35). xiii) At pH 7.4 the change in quaternary structure with fractional saturation of tetramers Y4 was constrained to be linear to within 5% between Y4 = 0 and Y4 = 0.5, in accord with results of NMR determinations (34).…”
Section: (31)supporting
confidence: 48%
“…xiii) At pH 7.4 the change in quaternary structure with fractional saturation of tetramers Y4 was constrained to be linear to within 5% between Y4 = 0 and Y4 = 0.5, in accord with results of NMR determinations (34).…”
Section: (31)mentioning
confidence: 54%
See 1 more Smart Citation
“…4). Also, it has been suggested that cooperativity can occur in the absence of a change in quaternary structure (14,39). Experimental results indicate that such a contribution to the cooperative oxygen binding, if it exists, is not important.…”
Section: Formulation Of the Modelmentioning
confidence: 67%
“…Spectroscopic studies of probes sensitive to specific changes are providing valuable information for testing models of cooperativity; an example is the attempt to distinguish between aand (3chain oxygenation by NMR (14,15) and by optical measurements (16). Highly accurate equilibrium measurements for oxygen binding in hemoglobin have been made under carefully controlled conditions (17,18); this removes some of the uncertainties present in the Roughton-Lyster data (19) on which the original fits were based.…”
mentioning
confidence: 99%